Striated agency and smooth regulation: kindergarten mealtime as an ambiguous space for the construction of child and adult relations. Issue 2 (4th March 2017) - Hansen, Stine Rosenlund; Hansen, Mette Weinreich; Kristensen, Niels Heine
ABSTRACT: Deploying an everyday life approach, this article focuses on the kindergarten meal, defined as a space in which humans, materials and discursive elements interact. The article identifies and discusses two co-existing perspectives on the everyday meals that emphasise children as future beings and here-and-now beings. Through the concepts of smoothing and striation the paper discusses how these perspectives produce different mechanisms of regulation and agency, and position the eaters differently. The paper emphasises kindergarten mealtime as an ambiguous space that does not offer simple discussions about good and bad meal situations. The paper thereby adds to the existing literature within children's geographies which emphasise interactional, relational and material aspects of children's lives. It does so by revisiting some concepts, striation and smoothing, that has been used to explore children's spaces and child–adult relations, but argue that these concepts describe ambivalent and complex processes in children's and adult's everyday lives.